(untitled) (Research, Society and Development, 2021)
Panfacial fractures are due to high-energy trauma, making the treatment of patients since the first visit is challenging. Generally, these involve soft tissue injuries, comminuted fractures and even fragment loss. In addition to this, the surgical approach to facial reconstruction through the fixation of bone fragments can be postponed due to the patient’s clinical conditions, which can lead the treatment to a more complex condition due to the possibility of infection, poor union of bone fragments and tissue contraction. The aim of this study is to discuss the clinical case of high-energy trauma caused by an air accident, leading to multiple facial and body fractures. And in this way contribute to the extremely limited scientific literature on the subject, with such etiology and significant facial trauma.